Effects of Pruning and Nitrogen Fertilization for The Rejuvenation and Physicochemical Characteristics Of Fruits of Declining Apricot Trees (Prunus Armeniaca L. CV. New Castle) (Bangladesh Journal of Botany, 2021)
Effects of pruning and nitrogen fertilization for the rejuvenation and physicochemical quality of fruits, bearing on declining apricot trees (Prunus armeniaca L. cv. New Castle) were assessed. Studies were conducted from 2011 to 2015 on the 25 years old senile and declining apricot trees. Ten treatments comprised of a factorial combination of three pruning levels/severity (heading back of main scaffolds at 20, 40 and 60%) with three levels of nitrogen doses (500, 625 and 750g N/tree). For the first time in the year 2011, the experimental trees received the treatments during its dormant period (winter). In the successive years, all the treatments were followed by corrective pruning facilitate rapid restoration of growth and production of the orchard. The factorial treatment combination of heavy pruning (60%) with the lowest doses of nitrogen level (500g/tree) increased the qualities of fruits in terms of weight, volume, firmness, total soluble solids, sugars and acidity content. Whereas, the ascorbic acid content was facilitated by heavy pruning (60%) with the highest doses of nitrogen level (750g/tree) in all the following years.Bangladesh J. Bot. 50(4): 1119-1126, 2021 (December)